Influence of supply chain risk management and its mediating role on supply chain performance: perspectives from an agri-fresh produce - Waqas, Umair; Abd Rahman, Azmawani; Ismail, Normaz Wana; Kamal Basha, Norazlyn; Umair, Sonia (Springer, 2022)
As agropreneurs of fresh fruits and vegetables are important contributors to the economy, supply chain risk management is vital for their survival and growth. Therefore, this study examined the mediating effect of supply chain risk management in reducing the impact of supply chain risks and increasing supply chain performance among small scale agropreneurs in Malaysia. It also evaluated the moderating role that knowledge management plays between supply chain risks and supply chain risk management. SmartPLS 3.0 (PLS-SEM), which uses partial least squares structural equation modelling, was utilised to test the framework. Data from 430 fresh fruit and vegetable agropreneurs in the five most productive Malaysian states were collected using a questionnaire. The results confirmed (1) a negative correlation between supply chain risks and supply chain performance (2) that supply chain risk management mediates the relationship between supply chain risks and supply chain performance, and (3) that knowledge management moderates the relationship between supply chain risks and supply chain performance. Therefore, these findings could help government institutes and agropreneurs associations better appreciate the value of supply chain risk management due to its positive effect on the overall performance of agropreneurships.